The rule of the function g (x) will be;
⇒ g (x) = - x + 3
What is mean by Translation?
A transformation that occurs when a figure is moved from one location to another location without changing its size or shape is called translation.
Given that;
g (x) is the indicated transformation of f (x).
The rule of f (x) is,
f (x) = - x + 5 ; horizontally translation 2 units left.
Now,
The rule of f (x) is,
f (x) = - x + 5 ; horizontally translation 2 units left.
Since, g (x) is the indicated transformation of f (x).
So, g (x) = f (x + 2)
Hence, We get;
g (x) = - (x + 2) + 5
= - x - 2 + 5
= - x + 3
Thus, The rule of the function g (x) will be;
⇒ g (x) = - x + 3
Learn more about the transformation visit:
brainly.com/question/1620969
#SPJ1
Answer:
-12 and 1
Step-by-step explanation:
If you multiply 12 by 1 you get 12, hence if you add -12 and 1 now you will get -11
Answer:
36.4mi
Step-by-step explanation:
The boat sailed two legs of a right-angled triangle.
The distance from the starting point is the hypotenuse of the triangle.
d = √(35² + 10²)
= √(1225 + 100)
= √1325
= 36.4 mi
Answer:
1. -5 and -8
2. -7 and -4
3. -15 and -1
4. 7 and -2
5. -5 and 1
6. 2 and -5
7. -8 and 9
8. 5 and -4
Step-by-step explanation: